ANALYSIS OF INTERNAL CONTROL SYSTEM AT PT ALBASIA INDO LESTARI PONTIANAK - Ellysa, Ellysa (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
ABSTRACT Inventory is one of the important assets owned by the company. Since inventory is an asset, a good and appropriate internal controls are required for the control and management of such merchandise to keep the inventory of the bad things that might happen in order for the business to continue operating.  The research method used is qualitative method with descriptive analysis by the data gained from in-depth interview with the owner of the business. From the results of research on PT Albasia Indo Lestari, author can conclude that the internal control of quite low. The lack of professional workers has been the main problem of the business. The practice in the business is also still need improvements and the business should also pay attention to its employees? knowledge and educations so their performances can be improved. There are still many improvements needed so the business can run effective and efficiently.   Keywords : evaluation, internal control system, inventory REFERENCESArnendo, B. Y. (2017). Analisis Pengaruh Pengendalian Intern dan Corporate Governance terhadap Fee Audit Eksternal Pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2012-2015). Retrieved from https://repository.usu.ac.id/handle/123456789/66939. Bragg, S. (2018). Inventory Cost. Retrieved from  https://www.accountingtools.com/articles/what-is-included-in-inventory-cost.html COSO. 2013. Committee of Sponsoring Organizations of the Treadway Commission. Retrieved from https://www.coso.org/Pages/ic.aspx Darmadi, Hamid. (2013). Metode Penelitian Pendidikan dan Sosial. Bandung : Alfabeta Denzin, N. K. & Lincoln, Y. S. (2013). Handbook of Qualitative Research Fourth Edition. California: SAGE Publications, Inc. Retrieved from http://libguides.usc.edu/writingguide/qualitative Gray, David. (2009). Doing Research in the Real World Second Edition. California: Sage Publications. Retrieved from https://www.ncbi.nlm.nih.gov/pmc/articles/PMC4194943/ Ikatan Akuntan Indonesia. (2016). Standar Akuntansi Keuangan. Jakarta. Kieso, D., Weygandt, J. & Warfield, T. (2013). Intermediate Accounting 15th Edition. New Jersey: Wiley. Krismiaji. (2002). Sistem Informasi Akuntansi. UPP AMP YKPN. Yogyakarta. McVay, Sarah. (2011). Inventory Management and Ineffective Internal. Retrieved from https://wpcarey.asu.edu/sites/default/files/sarah-mcvay.pdf. Napitupulu, I. H., Mahyuni, S. & Sibarani, J. L. (2016). The Impact of Internal Control Effectiveness to The Quality of Management Accounting Information System: The Survey on State-Owned Enterprises (SOEs). Retrieved from http://www.jatit.org/volumes/Vol88No2/18Vol88No2.pdf. Nurjanah, Siti. (2013). Analisis Sistem Pengendalian Internal Persediaan Pada Toko Wulan Salatiga. Perpustakaan Universitas Dian Nuswantoro : Semarang. Skripsi tidak dipublikasikan. Nurlaila, Isna. (2017). Evaluasi Penerapan Sistem Informasi Akuntansi dan Pengendalian Internal pada Persediaan Barang Jadi di PT. Iskandar Indah Printing Textile. Surakarta.  Rida, Fariyanti. (2014). Analisa Keefektifan Pengendalian Internal Sistem Persediaan pada PT Cassanatama Naturindo. Semarang.  Stice, E.K., Stice, J. D. & Skousen, K. F. (2008). Intermediate Accounting 17th Edition. Canada: South-Western Cengage Learning. Sulaiman, M., Siraj, S. A., & Ibrahim, S. H. M. (2008). Internal Control Systems in West Malaysia?s State Mosques. Retrieved from https://i-epistemology.net/v1/attachments/925_ajiss-25-1-stripped%20-%20Sulaiman%20and%20Siraj%20and%20Ibrahim%20-%20Internal%20Control%20Systems.pdf. Tampubolon, M.P. (2004). Manajemen Operasional. Jakarta: Ghalia Indonesia.